High-quality germanium growth on (111)-faceted V-groove silicon by molecular beam epitaxy - Yaonan Hou (Journal of Physics D: Applied Physics, 2024)
High-quality and low-defect-density germanium (Ge) buffer layers on silicon (Si) substrates have long been developed for group IV and III–V devices by suppressing defect propagation during epitaxial growth. This is a crucial step for the development of highly efficient photonic devices on Si substrates. Patterned silicon substrates have increasingly been employed for their ability to restrict and hinder the motion of defects. In this work, we demonstrate the effectiveness of an optimised two-step growth recipe structure on a (111)-faceted V-groove silicon substrate with a 350 nm flat ridge. This strategy successfully reduces the threading dislocation (TD) density while growing a 1 μm Ge buffer layer via molecular beam epitaxy. As a result, a high-quality buffer is produced with a low TD density on the order of 107 cm−2 and a surface roughness below 1 nm.